Hesperidin alleviates chronic restraint stress and lipopolysaccharide-induced Hippocampus and Frontal cortex damage in mice: Role of TLR4/NF-κB, p38 MAPK/JNK, Nrf2/ARE signaling. (November 2020) - Kwatra, Mohit; Ahmed, Sahabuddin; Gawali, Basveshwar; Panda, Samir Ranjan; Naidu, VGM
Abstract: Stress and lipopolysaccharide (LPS) animal models are used for screening antidepressants and anxiolytic drugs. However, the lacunae for their combination (Restraint stress; RS and LPS) impacting inflammation, apoptosis and antioxidant signaling have not been explored. The present study investigated RS + LPS-induced neurobehavioral and neurochemical anomalies in hippocampus (HIP) and frontal cortex (FC) of mice. Furthermore, citrus-derived flavanone glycoside (Hesperidin; HSP) neuroprotective ability was also confirmed in this model. Male Balb/c mice were given RS (for 28 days) and LPS (single dose, 0.83 mg/kg, i.p.) on 28 th day. RS + LPS challenge caused neurobehavioral deficits in mice as evaluated over elevated plus maze (EPM), open field test (OFT), light-dark box test, tail suspension test (TST), forced swim test (FST), sucrose preference test (SPT). Moreover, RS + LPS caused alteration via enhanced oxido-nitrosative stress, proinflammatory cytokines level (serum, HIP, FC), lower antioxidants (GSH, SOD, CAT), increased IBA-1, GFAP, TLR4/NF-κB, p38MAPK/JNK while decreased Nrf2/BDNF/HO-1 expression in HIP and FC of mice. The 21 days (8–28 th day), HSP (50 and 100 mg/kg, p.o.) treatment significantly alleviated the anxiety and depressive-like behavior and reversed neurochemical, histopathological changes. HSP exerted the neuroprotective effect via its anti-inflammatory, anti-apoptotic, antioxidant and neurogenesis potential in treating psychiatric illness alone or associated with other diseases. Graphical abstract: A Schematic pathway diagram of possible eventual events induced by chronic restraint stress (RS) and lipopolysaccharide (LPS) leading neurobehavioral and neurochemical deficits. Chronic stress and LPS induce oxido-nitrosative stress in microglia, hippocampus and cortical neurons, disrupt the NF-κB/Nrf2 balance and further activate the apoptotic pathway. Hesperidin (HSP) inhibits the inflammation, apoptosis and activates the antioxidant/BDNF signaling and succeeding neuronal survival in hippocampus and cortex of RS + LPS mice model. Image 1 Highlights: Chronic restraint stress (6h/day for 28 days) and single dose LPS (0.83 mg/kg)-induced neurobehavioral deficits in mice. Chronic restraint stress and LPS-induced oxido-nitrosative stress, NF-κB and p38 MAPK/JNK mediated apoptotic signaling. Chronic restraint stress and LPS downregulated Nrf2 mediated antioxidants and BDNF expression levels. Hesperidin ameliorated neurobehavioral and neurochemical deficits comparable to standard drug Fluoxetine. Hesperidin higher dose exhibited better neuroprotective effect and reversed the damage caused in hippocampus and frontal cortex.